Analisis Keterampilan Berbicara Menggunakan Buku Cerita Bergambar pada Siswa Kelas Tinggi - Alfiah Khairani; Andika Harizal Siregar; Manna Wassalwa; Juni Sahla Nasution (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to describe the speaking skills of high school students using picture story books. The method used in this research is literacy or literature review by collecting data sources relevant to the topic. The results of the research show that the use of picture story books as a learning medium has a significant impact on students' speaking abilities in high grades. Telling stories using picture books in peer groups can stimulate children's reasoning. Illustrations in storybooks are more effective in helping children understand the language and how it is conveyed compared to stories that only consist of text.